2021
DOI: 10.1016/j.asmr.2021.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Female and Younger Orthopaedic Sport Medicine Patients Are More Negatively Affected by COVID-19–Related Health Care Closures

Abstract: Purpose To determine if sex or age influence whether COVID-19 health care closures affect the health, recovery, and access to resources of pre- and post-operative orthopaedic sport medicine patients. Methods Electronic questionnaires assessing physical and emotional health, the value of virtual care, and access to resources were distributed to patients with postponed (PP) orthopaedic restorative surgeries and those within three-months post-operative (PO) at the time of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The included research articles were classified into five mutually exclusive primary focus areas during the data extraction phase: (1) access to and participation in sports , (2) access to SEM care , (3) health-related outcomes in SEM , (4) study methodology and (5) provider representation in SEM (table 1, online supplemental table S4). Most included studies were related to access to and participation in sports (n=45, 44%),17–61 followed by access to SEM care (n=28, 27%),62–89 health-related outcomes in SEM (n=24, 23%),90–113 provider representation in SEM (n=5, 5%)114–118 and methodology (n=1, 1%) 119…”
Section: Resultsmentioning
confidence: 99%
“…The included research articles were classified into five mutually exclusive primary focus areas during the data extraction phase: (1) access to and participation in sports , (2) access to SEM care , (3) health-related outcomes in SEM , (4) study methodology and (5) provider representation in SEM (table 1, online supplemental table S4). Most included studies were related to access to and participation in sports (n=45, 44%),17–61 followed by access to SEM care (n=28, 27%),62–89 health-related outcomes in SEM (n=24, 23%),90–113 provider representation in SEM (n=5, 5%)114–118 and methodology (n=1, 1%) 119…”
Section: Resultsmentioning
confidence: 99%
“…2 It is also consistent with recent data from preand postoperative sports medicine, which has shown that female patients more frequently report anxiety and concerns regarding COVID-19-related health care closures as compared with male patients. 11 Despite limited access to rehabilitation facilities and gymnasiums, patients were still able to undertake a variety of rehabilitation exercises, and many supplemented these with small equipment items, such as resistance bands and dumbbells. As might be anticipated, the frequency at which rehabilitation exercises were performed reduced as the time from surgery increased.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have reported on the clinical patterns of COVID-19 in athletic populations and provide valuable frameworks for optimal athlete recovery and care moving forward. 21 , 22 , 23 , 24 , 25 , 26 …”
Section: Iievolution Of Telehealth and Virtual Physical Examinationsmentioning
confidence: 99%
“…Female orthopaedic patients also appear to be more negatively impacted by pandemic-related physiotherapy facility closures, reporting significantly more pain, anxiety, and delayed recovery during rehabilitation. 22 Therefore, identifying various demographic trends in the clinical presentation of athletes with COVID-19 may further aid in the early management of the disease and limiting community transmission.…”
Section: Iievolution Of Telehealth and Virtual Physical Examinationsmentioning
confidence: 99%